Legal construction as a category of cybernetic method of cognition of law - Purge, Anna Rolandovna (Право и политика, 2023)
The object of the study is social relations, the regulation of which is carried out by establishing a legal structure. The subject of the research is the legal concepts of legal science, which allow designing and using cybernetic categories of modeling legal situations and phenomena in the legal field. The concept of legal construction is the result of applying a certain cybernetic method of cognition of law. One of the methods related to the tools of this method is the method of modeling. In other words, a legal construction is a model obtained as a result of applying a cybernetic modeling method to a public relation (or rather, to the method of legal regulation of this type of public relations). Among the methodological problems of the modern general theory of law, the problem of legal discourse stands out, i.e. the practical language spoken by law (the language of legal constructions), and the theoretical language in which they talk about law (the language of legal concepts). On the other hand, modern law-making activity requires the use of a variety of methods of legal regulation, the improvement of legal technology, allowing the best way to express the will of the legislator, contributing to the simplification and acceleration of the implementation and application of law. Such legal means include legal constructions. The paper substantiates the approach according to which the concept of legal construction is the result of applying a certain cybernetic method of cognition of law.